AUDIT MUTU HUKUM PERATURAN DAERAH : Model Evaluasi Antisipatif Produk Hukum Pemerintah Daerah yang Kondusif bagi Penagaman Modal dan Daya Saing Investasi - FC Susila Adiyanta (Faculty of Law, Universitas Diponegoro, 2010)
Implementation of autonomy and decentralization, in practice local authorities carry broad implications for managementofregionalautonomyfrom various aspects. One of the many urgent problems to be overcome by such local government is the emergence of regional regulations and other regulations of products made by local governments that are not conducive to the business climate, attracting no capital investment and competitive for investment competitiveness, both in local and national context